(untitled) (International Journal of Educational Management, Rivers State University., 2025)
This study investigated funding and non-funding partnership between universities and industries for sustainable development in River State. Two research questions and two null hypotheses guided the study. Descriptive survey research design was adopted. The population for the study is two thousand, three hundred and seventy-three (2,373) university administrative staff and chief executive officers of industries. This is made up of 668 universities administrative staff and 1705 Chief Executive Officers of industries in Rivers State. The sample size was 894 (467 universities administrative staff and 427 CEOs). The sample was drawn through multistage sampling procedure using cluster and disproportionate stratified random sampling techniques. University and Industry Partnership Questionnaire was used for data collection. Face and content validities were ensured by experts in measurement and evaluation. Internal consistency was through Cronbach alpha gave reliability coefficient of 0.89. Mean, standard deviation and z-test were used for data analysis. It was found among others that funding and non-funding partnership between universities and industries for sustainable development includes: commercialization of research, endowments, grants, university-productive sector linkages and contribution to tertiary education trust fund, educational collaborations, academic entrepreneurship, establishment of multi-disciplinary research centers and students’ internship. The study recommends among others that; universities should develop functional websites where they can advertise and market their research findings; intellectual property and sale of products of technologies to industries. The university should always sign a memorandum of understanding with any industry of interest on the modus operandi in order not to have a bridge of contract.